SEJARAH PERADABAN ISLAM ; MADRASAH NIDZAM AL- MULK - Amrullah, fikri (Humanistika : Jurnal Keislaman, 2019)
Abstract: This paper takes into account the first boarding school have been expanding in Baghdad and  being sample to other boarding school in curriculum and system has purposed. That is Nidzamul Mulk boarding school. curriculum and system used refer in modern curriculum , same in technology system or the teach of lesson but al-Qur’an first of orientation. Name of this Nidzamul Mulk boarding school is takes from the leader Nidzam al-Mulk. He is master of dinasti salajikah child ali bin ishaq at-tusi. His father educated Nidzam al-Mulk be hard. Being Nidzam al-Mulk some have high education and be popular about the knowledge. So that’s Nidzam al-Mulk is very popular in that’s countries and high knowledge until he have wanted to building the boarding school. Keyword : Boarding school, al-Qur’an, curiculum